Food safety aspects on ethnic foods: toxicological and microbial risks. (December 2015) - Fusco, Vincenzina; Besten, Heidy MW den; Logrieco, Antonio F; Rodriguez, Fernando Perez; Skandamis, Panagiotis N; Stessl, Beatrix; Teixeira, Paula
Highlights: Ethnic foods outbreaks and recalls are rising worldwide. Listeria and Salmonella outbreak linked to Asian foods, Mexican-style/French cheeses. Common recalls: pathogens, mycotoxins, unlabeled allergens, hazardous chemicals. There is need for risk assessment and setting mitigation strategies for ethnic foods. Abstract : Ethnic foods are becoming popular worldwide. Nevertheless, foodborne outbreaks and food recalls due to the contamination of these foods with pathogenic agents, toxins, undeclared allergens and hazardous chemical compounds are increasing in recent years together with their growing popularity. In this context, ad hoc prevention and control strategies are needed, to assess and face the emerging microbiological and toxicological risks associated with the consumption of ethnic foods.